The Effects of Natural Clinoptilolite and Nano-Sized Clinoptilolite Supplementation on Lipid Profile, Food Intakes and Body Weight in Rats with Streptozotocin-Induced Diabetes - Behnoush Hossein-Nia; Sirous Khorram; Hassan Rezazadeh; Abdolrasol Safaiyan; Rafighe Ghiasi; Ali Tarighat-Esfanjani (Tabriz University of Medical Sciences, 2018)
Purpose: To determine the effect of natural clinoptilolite (CLN) and nano-sized clinoptilolite (NCLN) on lipid profile, food intakes (FI) and weight changes in streptozotocin (STZ) induced diabetic rats. Methods: In this experimental study, 36 rats were randomly divided into two groups: diabetic group which was injected STZ (60 mg/kg BW), and a non-diabetic group. Three days after diabetes induction, each of these groups was randomly divided into 3 subgroups of 6 animals ((1) control, (2) 1%/food CLN, (3) 1%/food NCLN). The animals were supplemented for 28 days, starting three days after STZ administration. At the end of the study, blood was drawn for biochemical assays. The weights and FIs of the rats were measured at the beginning and end of each week. Results: Our findings revealed that there was no significant change in lipid profile, 28 days after administration of STZ in diabetic rats. Low density lipoprotein (LDL) was increased slightly in diabetic rats treated with NCLN without any significant changes in other lipid profile parameters in the other groups. Weight was reduced significantly in diabetic rats. Administration of CLN and NCLN prevented further weight loss in diabetic rats. All groups treated with STZ had higher food intake during the study. Conclusion: Lack of beneficial changes in lipid profile may be attributed to short study duration, insufficient for appearance of lipid abnormalities. Given the partial improvement in weight status and lack of undesirable effects of clinoptilolite supplementation, further research is recommended in subjects with typ1 diabetes mellitus.